DEVELOPING MOBILE-ASSISTED LANGUAGE LEARNING (MALL) MATERIALS TO LEARN DESCRIPTIVE TEXTS - Sanjaya, Eko; Salam, Urai; Ikhsanudin (ELLTER Journal, 2024)
The current study aimed to develop MALL materials for descriptive texts to support students’ learning outside classroom hours as supplementary materials. The researcher applied the ADDIE model to carry out the research. The study participants were 17 students of SMPN 4 Satu Atap Sejangkung. Students used the developed product outside school hours as supplementary materials to support what they have learned at school. Interviews for students’ needs and opinions and experts’ judgments were used to collect the research data. The study revealed the students’ needs for MALL materials, the MALL materials were applicable according to the experts, and students had positive opinions towards the MALL materials. Overall, the study was successful in developing MALL materials as supplementary materials to support 7th-grade students of SMPN 4 Satu Atap Sejangkung in learning descriptive texts.